Analisis Kedisiplinan Kerja Pegawai di Kantor Urusan Agama Wringin Kabupaten Bondowoso - Novitasari Novitasari; Nike Septiana Iswandari; Hoirul Amin; Aniqotuzzuhro' Fitriana (Medan Resource Center, 2023)
This journal focuses on how the disciplinary work ethic between civil servants and non-PNS employees at the Wringin Religious Affairs Office, Bondowoso Regency. The purpose of this journal is to find out whether PNS and non-PNS employees at the Office of Religious Affairs (KUA) of Wringin District, Bondowoso Regency are disciplined or not in carrying out the tasks that have been given. The type of research used in this research is a descriptive qualitative approach, while in data collection techniques using interviews, observation, and documentation. Based on the results of the observations that we have made, it can be concluded that the discipline of PNS and non-PNS employees at the Office of Religious Affairs in Wringin District, Bondowoso Regency can be said to be good, this is in accordance with Government Regulation Number 94 of 2021.